Bulut Bilişimin Muhasebe Mesleği Üzerindeki Etkileri - Açık Taşar, Sezin; Demir, Özcan (Muş Alparslan Üniversitesi, 2020)
Information technologies which have become a significant part of our daily life have been more important in many areas such as education, business world and health. The importance of information technologies is greater by maintaining competitiveness, reducing costs and reaching global markets. As in all departments of companies, new business models have emerged within the scope of data mining in using and processing of the data in the accounting department. This situation means that cloud computing will become more widespread. In our study, the importance and effects of cloud computing in accounting were indicated. It is aimed that business managers in a global competitive environment know and choose cloud accounting by comparing the differences between traditional accounting and cloud computing.

Güncel yaşantımızın önemli bir parçası haline gelen bilişim teknolojileri; eğitim, iş dünyası, sağlık gibi pek çok alanda gün geçtikçe önemini artırmaktadır. Bilişim Teknolojileri işletmeler açısından özellikle rekabet gücünü koruyabilmesi, maliyetlerin düşürülmesi ve global pazarlara erişilmesi bakımından taşıdığı önem hiç şüphesiz daha da büyüktür. İşletmelerin tüm bölümlerinde olduğu gibi muhasebe bölümünde de verilerin kullanımı ve işlenmesinde veri madenciliği kapsamında yeni iş modelleri ortaya çıkmıştır. Bu durum, bulut bilişimin gün geçtikçe daha fazla yaygınlaşacağı anlamını taşımaktadır. Çalışmamızda muhasebe alanında bulut bilişimin önemi ve etkileri gösterilmeye çalışılmış, geleneksel muhasebe ile bulut bilişim arasındaki farklılıklar ortaya koyularak, global rekabet ortamında yer alan işletme yöneticilerinin bulut muhasebe yazılımları ile ilgili bilgi sahibi olmaları ve doğru yazılımı seçmeleri hedeflenmiştir.
Effects of Cloud Computing on Accounting Profession
anemon
Keywords: Cloud Computing; Traditional Accounting; Cloud Accounting; Bulut bilişim; geleneksel muhasebe; bulut muhasebe